Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1177/0075424202026002974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Temperature on Water Absorption Coefficient of Building Materials

Abstract: Vous avez des questions?Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Effect of surface temperature on water absorption coefficient of building materials M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 1 publication
(3 reference statements)
2
24
0
5
Order By: Relevance
“…Mukhopadhyaya et al confirmed the temperature influence on capillary absorption coefficient of brick specimens in his study with different porous materials [16]. In order to minimize the effect of temperature on our results, tests were performed in a room with controlled temperature.…”
Section: Introductionmentioning
confidence: 72%
“…Mukhopadhyaya et al confirmed the temperature influence on capillary absorption coefficient of brick specimens in his study with different porous materials [16]. In order to minimize the effect of temperature on our results, tests were performed in a room with controlled temperature.…”
Section: Introductionmentioning
confidence: 72%
“…Currently researchers from the Institute for Research in Construction (IRC) are looking at the possibility to incorporate temperature effects on the moisture (both liquid and vapor) transport properties of building materials into the moisture management strategy. As a part of it, recent studies at the IRC [13] established that higher surface temperature of the material causes higher liquid moisture diffusion into 'eastern white pine wood'. However, negligible or little effects were found on liquid moisture diffusion in the same study when the materials were 'red clay brick' or 'concrete'.…”
Section: Research Background and Significancementioning
confidence: 99%
“…There was no significant difference between the results of the two planes. The absorption coefficient for the chestnut was lower than that of the pine, 1.1x10 -2 kg·m -2 ·s -0.5 (Mukhopadhyaya et al 2002). Even though the coatings had an organic solvent base, the water absorption coefficient can be considered an indication of the mechanisms for liquid absorption which could explain the differences between chestnut and pine.…”
Section: Resultsmentioning
confidence: 93%